A case of missed giant bullae emphysema diagnosed as pneumothorax - Ong, SF; Nik Azlan Nik Muhamad, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
We report a case of a giant bullous emphysema misdiagnosed as a pneumothorax. A 18-year-old chronic smoker presented with right sided chest pain and dyspnoea. Initial respiratory rate was 35 /min, blood pressure was 136/90 mmHg, heart rate 80/min and SpO2 was 98% on room air. Clinical examination revealed reduced right air entry and left trachea deviation. Chest X-ray helped to arrive at a diagnosis of pneumothorax. Needle aspiration was then performed followed by a chest tube thoracostomy because of no improvement. Massive amount of blood was drained and patient deteriorated further. CT thorax revealed a right haemopneumothorax with multiple bullaes. Patient was rushed to OT for emergency thoracotomy for stapling of the ruptured bullae. Giant bullous emphysema can mimic pneumothorax and physician must be vigilant if draining a suspected pneumothorax.